Clostridium Perfringens Bacteremia with Acute Hemolytic Anemia in the Setting of Endometrial Malignancy. Issue 1 (March 2019) - Cypher, Luke R.; Sullivan, Christopher; Jones, Ryan; Phillips, Angelina
Acute intravascular hemolysis is a rare and often lethal complication of Clostridium perfringens septicemia.Clostridium perfringens is an anaerobic, gram-positive spore-forming rod which is commonly implicated in cases of food poisoning, gas gangrene, and severe hemolytic anemia in humans via the alpha-toxin (phospholipase C). We report an interesting and rare case of a 72-year-old woman who developed massive intravascular hemolysis secondary to C perfringens bacteremia in the setting of poorly differentiated high-grade endometrial malignancy.